Current Trends in Human Trafficking and the Effectiveness of Law Enforcement Strategies in Combating Sex Trafficking in Thailand - Kanchana Thammasiri (Studies in Social Science & Humanities, 2024)
This paper examines the current state of sex trafficking in Thailand, focusing on recent trends, law enforcement strategies, and challenges faced in combating this pervasive issue. Thailand has established a comprehensive legal framework to address human trafficking, including significant legislation and international commitments. Law enforcement employs a range of strategies, including surveillance, undercover operations, and inter-agency collaboration, to dismantle trafficking networks and support victims. However, challenges such as corruption, resource limitations, and the complexity of trafficking networks hinder these efforts. The paper also provides recommendations for improving law enforcement capabilities, victim support, legal frameworks, international cooperation, and the use of technology to enhance anti-trafficking measures. By addressing these areas, Thailand can strengthen its fight against sex trafficking and provide better protection for vulnerable individuals.